A New S4 Flavor Symmetry in 3-3-1 Model with Neutral Fermions - V. V. Vien; H. N. Long (Advances in High Energy Physics)
A new S4 flavor model based on SU(3)C⊗SU(3)L⊗U(1)X gauge symmetry responsible for fermion masses and mixings is constructed. The neutrinos get small masses from only an antisextet of SU(3)L which is in a doublet under S4. In this work, we assume the VEVs of the antisextet differ from each other under S4 and the difference of these VEVs is regarded as a small perturbation, and then the model can fit the experimental data on neutrino masses and mixings. Our results show that the neutrino masses are naturally small and a deviation from the tribimaximal neutrino mixing form can be realized. The quark masses and mixing matrix are also discussed. The number of required Higgs multiplets is less and the scalar potential of the model is simpler than those of the model based on S3 and our previous S4 model. The assignation of VEVs to antisextet leads to the mixing of the new gauge bosons and those in the standard model. The mixing in the charged gauge bosons as well as the neutral gauge bosons is considered.